Co-substrate model development and validation on pure sugars and corncob hemicellulosic hydrolysate for xylitol production - Juan Feng; Charin Techapun; Yuthana Phimolsiripol; Pornchai Rachtanapun; Suphat Phongthai; Julaluk Khemacheewakul; Siraphat Taesuwan; Kritsadaporn Porninta; Su Lwin Htike; Chatchadaporn Mahakuntha; Sumeth Sommanee; Rojarej Nunta; et al. (Scientific Reports)
Abstract A co-substrate model of Candida tropicalis TISTR 5306 cultivated in 10 - 100 g/L xylose and 1 - 10 g/L glucose at the ratio of 10:1 was developed based in part on modified Monod equation. The kinetic parameters include substrate limitation as well as substrate and product inhibitions with inclusion of threshold values. A general good fitting with average RSS total , R 2 , and MS total values of 162, 0.979, and 10.8, respectively, was achieved between ten simulated profiles and experimental kinetics data. The implementation of developed model on xylitol production from non-detoxified corncob hemicellulosic hydrolysate resulted in relatively good agreement with RSS total , R 2 , and MS total values of 368, 0.988, and 24.5, respectively. The developed model can be applied to predict microbial behavior in batch xylitol production system using hemicellulosic hydrolysate over a xylose range of 10 - 100 g/L and provide useful information for subsequent design of fed-batch and continuous systems to achieve the efficient sustainable resource management of this agricultural and agro-industrial waste.